Pengaruh Kepemimpinan Penjabat Kepala Desa Dalam Pemerintahan Desa Haurngombong - Abdul Rohman; Yadi Supriyadi; Nurul Huda (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2021)
This article discusses the leadership influence of the Acting Village Head who acts as a leader in the Haurngombong Village Government, Pamulihan District, Sumedang Regency. The presence of the Acting Village Head as a result of the resignation of the definitive Village Head in the village is a highlight of the focus of this research topic. With an emphasis on knowing the influence in leading, in addition to trying to discuss the satisfaction of the community with the official's leadership. This study uses a juridical normative research method, with a qualitative approach. Furthermore, bibliographical materials in the form of legislation and other data sources are analyzed to obtain results as accurate as possible. The results of this study include: (1) The task of the government is optimal community service, based on the fourth paragraph of the Preamble to the 1945 Constitution as the state's goal for the welfare of the community. (2) The basis for implementing Village Government is regulated in the Village Law. (3) the influence of the leadership of the Acting Village Head in Haurngombong Village is enormous, especially the leadership of Mr. Zaman who always provides efficient and pro-people innovations is considered to have succeeded in leading the people of Haurngombong Village optimally. Both the village community and village officials were very satisfied with the leadership of Mr. Zaman as the Acting Village Head in the Haurngombong Village Government of Sumedang Regency.